2022
DOI: 10.3390/min12091172
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Study on the Relationships between Mineralized Structures and Induced Polarization Properties of Seafloor Polymetallic Sulfide Rocks

Abstract: The induced polarization (IP) method plays an important role in the detection of seafloor polymetallic sulfide deposits. Numerical simulations based on the Poisson–Nernst–Planck equation and the Maxwell equation were performed. The effects of mineralized structures on the IP and electrical conductivity properties of seafloor sulfide-bearing rocks were investigated. The results show that total chargeability increases linearly as the volume content of disseminated metal sulfides increases when the volume content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…( 11), which is 0.063. Wu et al (2022) reported related results to this; through numerical simulation, they calculated the chargeability for 0.7 with φ m = 0.1 of massive sulfide ore. The observed discrepancy between the chargeability values calculated using Eq.…”
Section: Specifying General Trends and Geometric Influences On Charge...mentioning
confidence: 90%
See 1 more Smart Citation
“…( 11), which is 0.063. Wu et al (2022) reported related results to this; through numerical simulation, they calculated the chargeability for 0.7 with φ m = 0.1 of massive sulfide ore. The observed discrepancy between the chargeability values calculated using Eq.…”
Section: Specifying General Trends and Geometric Influences On Charge...mentioning
confidence: 90%
“…Equation ( 11) assumes spherical sulfide grains (e.g., Revil et al 2018 ;Revil and Gresse 2021), but real sulfides often have varied shapes like flattened ellipsoids, influencing the IP effect (Zhdanov et al 2008;2012). Moreover, Wu et al (2022) indicates that massive and veined sulfides in rocks create extended electron paths, thereby enhancing conductivity. Nevertheless, the low-frequency polarization of these sulfides obstructs the primary current, leading to significant conductivity losses and an increase in chargeability.…”
Section: Specifying General Trends and Geometric Influences On Charge...mentioning
confidence: 99%